The effect of eccentric drilling on formation damage to berea sandstone formation - Teow, Ket Seang (2003)
Formation damage caused by particles and filtrate invasions has been identified as one of the major problems that cause serious damage to the formation, thus it results in reduction of oil and gas productivity. It occurs throughout the life of an oilwell, especially during drilling a horizontal well. In a horizontal well, drill string eccentricity phenomenon tends to occur mostly due to the gravitational effect and this phenomenon would contribute to formation damage. A formation damage rig with 6" hole and 3.5" drill string simulating a slim-hole drilling had been designed to facilitate the investigation of damage on Berea sandstones caused by oil-based mud in dynamic condition at various differential pressures, drill string rotations, and exposure times. The rig was also used to investigate the damage of Berea sandstones in horizontal and vertical wells. The experimental results showed that the drill string eccentricity did contribute to the permeability reduction and became critical as differential pressure, drill string rotation speed, and exposure time were increased. The eff~ct of drill string eccentricity at 250 psi induced differential pressure encountered lesser permeability impairment compared to 200 psi. SEM studies showed the presence of micro fractures in the cores when exposed to differential pressure of250 psi, which increases the permeability of the Berea sandstones (improved permeability). SEM visualization revealed that the particles plugging and deposition in pore spaces in horizontal well was found to be more severe than vertical well, thus it induced higher damage in the former well